2006
DOI: 10.1021/es060908a
|View full text |Cite
|
Sign up to set email alerts
|

Polar Pollutants Entry into the Water Cycle by Municipal Wastewater:  A European Perspective

Abstract: The effluents of eight municipal wastewater treatment plants (WWTP) in Western Europe were analyzed by liquid-chromatography-mass spectrometry for the occurrence of 36 polar pollutants, comprising household and industrial chemicals, pharmaceuticals, and personal care products. In a long-term study of the effluents of three WWTP over 10 months, sulfophenyl carboxylates and ethylene diamino tetraacetate (EDTA) were detected above 10 microg/L on average, while benzotriazoles, benzothiazole-2-sulfonate, diclofenac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
196
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(216 citation statements)
references
References 30 publications
11
196
1
8
Order By: Relevance
“…OPEs cannot be efficiently removed by conventional biological treatment processes in wastewater treatment plants (WWTPs), resulting in their widespread presence in secondary effluents and surface waters at concentrations ranging from ng L À1 to a few hundred lg L À1 [4][5][6]. Marklund et al [7] identified tris (2-butoxyethyl) phosphate (TBEP), tris(chloropropyl) phosphate (TCPP) and tri-n-butyl phosphate (TnBP) as the most abundant OPEs at concentrations ranging from 0.36 to 30 lg L À1 in the effluents of seven Swedish WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…OPEs cannot be efficiently removed by conventional biological treatment processes in wastewater treatment plants (WWTPs), resulting in their widespread presence in secondary effluents and surface waters at concentrations ranging from ng L À1 to a few hundred lg L À1 [4][5][6]. Marklund et al [7] identified tris (2-butoxyethyl) phosphate (TBEP), tris(chloropropyl) phosphate (TCPP) and tri-n-butyl phosphate (TnBP) as the most abundant OPEs at concentrations ranging from 0.36 to 30 lg L À1 in the effluents of seven Swedish WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…Removal efficiencies in conventional WWTPs have been reported to be in the ranges of 13e62% for BT and 11e74% for 5-TTri (Hollingsworth et al, 2005;Giger et al, 2006;Voutsa et al, 2006;Weiss et al, 2006), with no published data available for CBT. Benzotriazole has been detected in surface water at concentrations up to 3.4 mg/L (Breedveld et al, 2003;Weiss and Reemtsma, 2005;Giger et al, 2006;Reemtsma et al, 2006;Voutsa et al, 2006;Weiss et al, 2006;Kiss and Fries, 2009), in sediment and sludge at concentrations up to 198 ng/g (Zhang et al, 2011). Much higher concentrations of up to 126 mg/L for BT and 17 mg/L for 5-TTri have been found in groundwater from airport locations due to its heavy use as an antifogging agent (Cancilla et al, 1998(Cancilla et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…So, what do we know about what chemicals are present in this effluent, and at what concentrations? The answer appears to be 'very little' (Reemstsma et al 2006). We know quite a lot about some chemicals, or groups of chemicals (e.g.…”
Section: What Do We Know About Exposure?mentioning
confidence: 99%